Exploring teachers - Nurfaidah, Sitti; Khairunnisa, Ulfah; Syukri, Suhartini; Jamilarin, Patrick Anthony P. (Journal on English as a Foreign Language, 2024)
Despite the growing body of research on corrective feedback in foreign language learning, there remains a gap in understanding the specific strategies utilized by EFL teachers as observed by pre-service teachers firsthand. Based on the observed experiences of EFL pre-service teachers during their observational field teaching practice, this study aims to analyze how English teachers give their corrective feedback. This study employed a qualitative research approach with a case study design. Eleven Indonesian EFL pre-service teachers who had finished their field teaching practice were involved in the study. The qualitative data were gathered using reflective Focus Group Discussions (FGD) and semi-structured interviews. The result of qualitative data analysis revealed three emerging themes of teachers